Kualitas dan nilai ekonomis nugget pada berbagai proporsi penggantian daging ayam dengan tahu: The quality and economic value of nugget at various substitution proportion chicken meat by tofu - Ira SK Puarada; Siti Ch. Chotimah; Amrih L Killian (Fakultas Peternakan Universitas Papua, 2007)
The aim of the research was observing the effect of substituting chicken meat as main material in nugget production with tofu on nugget quality and its production cost. The research was design in Complete Random Design with four compositions of c hicken meat and tofu as nugget production material, i.e., A=100% chicken meat; B= 85% chicken meat and 15% tofu; C=70% chicken meat and 30% tofu; D = 55% chicken meat and 45% tofu. Nugget quality tested based on its water content and cooking loose. The eco nomical value of substituting chicken meat with tofu tested based on its production cost reduction and Break Event Point at each material composition. The result showed that substituting chicken meat with tofu was very significantly affected the nugget wat er content (P<0.01), and was significantly affected its cooking loose (P<0.05). Moreover, the production cost and break event point was lower with the higher proportion of tofu in material. However, the optimum quality and production cost of the nugget was at 85% chicken meat and 15% tofu.